Developing an Integrated Child-Friendly Pesantren Model: Bridging Indonesian and Egyptian Islamic Boarding Education - Imron Fauzi; Aminulloh; Mohammad Mu'tashim Billah (Journal of Islamic Education Research, 2026)
This study aims to develop an Integrated Child-Friendly Pesantren Model by examining how Indonesian local Islamic educational practices can be strengthened through dialogue with Egyptian Islamic educational traditions, particularly the Al-Azhar system. Employing a qualitative multiple-case-study design within an interpretivist paradigm, data were collected through participant observation, semi-structured interviews, and document analysis at Pesantren Nurul Qornain Sukowono and Pesantren Nurul Islam 1 Jember, East Java, Indonesia. The findings were interpreted through a comparative framework informed by educational principles associated with Al-Azhar institutions in Egypt and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal four interconnected components of child-friendly Islamic boarding education: preventive habituation, relational protection, meaningful participation, and Islamic moral governance. Preventive habituation promotes self-regulation through structured routines; relational protection ensures emotional safety through trust-based teacher–student relationships; meaningful participation strengthens belonging and social responsibility; and Islamic moral governance integrates adab, akhlaq, amanah, and rahmah into institutional leadership and educational management. The novelty of this study lies in the development of the Integrated Child-Friendly Pesantren Model, which extends the Child-Friendly School framework by synthesizing Indonesian pesantren traditions with comparative insights from Egyptian Islamic education. This study contributes a culturally grounded and internationally relevant framework for child protection, student well-being, character development, and value-based governance in contemporary Islamic boarding schools.